Anti-CD74 IgA autoantibodies in radiographic axial spondyloarthritis: a longitudinal Swedish study. (28th December 2020) - Do, Lan; Granåsen, Gabriel; Hellman, Urban; Lejon, Kristina; Geijer, Mats; Baraliakos, Xenofon; Witte, Torsten; Forsblad-d'Elia, Helena
Abstract: Objectives: Antibodies against anti-CD74 are related to axial spondyloarthritis (axSpA). The objectives were (i) to study IgA anti-CD74 in radiographic (r)-axSpA patients in the Backbone cohort and to calculate the sensitivity and specificity of anti-CD74, (ii) to study the fluctuation of IgA anti-CD74 levels in prospectively collected samples, and (iii) to explore the relation between IgA anti-CD74 and radiographic spinal changes. Methods: IgA anti-CD74 was analysed by ELISA in 155 patients with r-axSpA and age- and sex-matched controls. BASDAI, ASDAS, BASFI and BASMI were assessed and spinal radiographs were scored for r-axSpA-related changes with mSASSS. Previously donated samples, before inclusion in the Backbone study, were identified in the Medical Biobank of Northern Sweden. Results: A total of 155 patients comprising 69% men and 31% women, age [mean (s .d .)] 55.5 (11.4) years and 152 (98.1%) HLA-B27 positive, were included. The plasma level of IgA anti-CD74 was significantly higher in the patients [median (interquartile range), 12.9 (7.9–17.9) U/ml] compared with controls [10.9 (7.2–14.6) U/ml, P  = 0.003]. IgA anti-CD74 was above the cut-off level of 20 U/ml in 36/155 (23.2%) patients and in 15/151 (9.9%) controls ( P  = 0.002). Multivariable logistic regression analyses revealed ≥1 syndesmophyte associated with IgA anti-CD74 (odds ratio 5.64; 95% CI: 1.02, 35.58; P  = 0.048) adjusted for hsCRP, smoking, BMI, sex and age. No distinct pattern of IgA anti-CD74 over time was revealed. Conclusion: Plasma levels of IgA anti-CD74 were increased in r-axSpA and independently associated with radiographic spinal changes, which suggests that IgA anti-CD74 could play a role in the pathogenies of r-axSpA.